2012
DOI: 10.1128/jb.00288-12
|View full text |Cite
|
Sign up to set email alerts
|

Oxalyl-Coenzyme A Reduction to Glyoxylate Is the Preferred Route of Oxalate Assimilation in Methylobacterium extorquens AM1

Abstract: Oxalate catabolism is conducted by phylogenetically diverse organisms, including Methylobacterium extorquens AM1. Here, we investigate the central metabolism of this alphaproteobacterium during growth on oxalate by using proteomics, mutant characterization, and 13 C-labeling experiments. Our results confirm that energy conservation proceeds as previously described for M. extorquens AM1 and other characterized oxalotrophic bacteria via oxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 68 publications
2
27
0
1
Order By: Relevance
“…Exported formate can subsequently be oxidized by the periplasmic dehydrogenase Fdh3, which was up-regulated during plant colonization. Previous characterization of the oxalate metabolism in M. extorquens AM1 revealed that reduction of oxalyl-CoA to glyoxylate is the preferred route of oxalate assimilation and that NAD(P) ϩ transhydrogenase for redox balance was highly expressed in cells grown on oxalate (52). In the present study, NAD(P) ϩ transhydrogenase was induced upon plant colonization in M. extorquens PA1, however, the corresponding proteins for assimilatory reduction to glyoxylate were down-regulated, indicating that oxalate oxidation is rather used for energy conservation than for carbon assimilation (supplemental Table S3).…”
Section: Swath Assaymentioning
confidence: 99%
“…Exported formate can subsequently be oxidized by the periplasmic dehydrogenase Fdh3, which was up-regulated during plant colonization. Previous characterization of the oxalate metabolism in M. extorquens AM1 revealed that reduction of oxalyl-CoA to glyoxylate is the preferred route of oxalate assimilation and that NAD(P) ϩ transhydrogenase for redox balance was highly expressed in cells grown on oxalate (52). In the present study, NAD(P) ϩ transhydrogenase was induced upon plant colonization in M. extorquens PA1, however, the corresponding proteins for assimilatory reduction to glyoxylate were down-regulated, indicating that oxalate oxidation is rather used for energy conservation than for carbon assimilation (supplemental Table S3).…”
Section: Swath Assaymentioning
confidence: 99%
“…Several intermediates of the L-arabinose degradation pathway (L-2-keto-3-deoxyarabonate, glycolaldehyde, and glyoxylate) as well as oxalate could be identified by a metabolomics approach (using nanoflow ion-pair RP-HPLC coupled with nanospray high-resolution MS with a split-free nano-LC Ultra system connected to an LTQ-Orbitrap mass spectrometer). Sampling, quenching, and central metabolite extraction were carried out as described by Schneider and colleagues (32). The data were normalized to the biomass produced in the cultures.…”
Section: Methodsmentioning
confidence: 99%
“…The oxalate-grown organisms also contained L-serine-glyoxylate aminotransferase and hydroxypyruvate reductase, indicating that synthesis of C 3 -compounds from oxalate occurred by a variant of the serine pathway ''used by Pseudomonas AM1 during growth on C 1 -compounds'' (Blackmore and Quayle 1970). This metabolism was subsequently confirmed for other Methylobacterium species and for Mtb extorquens strain AM1 (Schneider et al 2012), and the mechanism of oxalate oxidation and assimilation is available on the MetaCyc database for Mtb extorquens (http:// metacyc.org/META/NEW-IMAGE?type=NIL&object=PWY-6696) and Mtb chloromethanicum (http://biocyc.org/MCHL440085/ NEW-IMAGE?object=Oxalate-Degradation).…”
Section: Physiologymentioning
confidence: 77%